THE DEVELOPMENT OF THE THEORY OF ELECTORAL BEHAVIOR IN DOMESTIC AND FOREIGN POLITICS - Egor Alekseevish Ravin (Современная наука и инновации)
In the article author analyze of the main approaches to the study of electoral behavior in Russia and abroad. The democratization of the elections to the Institute of actual, not mythological or manipulated the will of the sovereign power - the people, the task of any state.